The second wave of formose research - Akihito Hashidzume (BBA Advances)
This review article highlights key developments in the second wave of formose research (from approximately 2000), summarizing approximately 100 relevant studies. Section 1 introduces the basics of formose reaction and its historical context. Section 2 provides a brief overview of the pioneering works from the first wave of formose research (from 1970 to 1990). Section 3 then overviews the second wave of formose research, in which formose reactions under various conditions, mechanistic studies of the formose reaction, formose reactions and the origin of life, and applications of formose reactions are described. Finally, Section 4 offers summary and outlook.